2020
DOI: 10.1002/chem.201905238
|View full text |Cite
|
Sign up to set email alerts
|

An Air‐Stable, Neutral Phenothiazinyl Radical with Substantial Radical Stabilization Energy

Abstract: The vital effect of radical states on the pharmacological activity of phenothiazine‐based drugs has long been speculated. Whereas cationic radicals of N‐substituted phenothiazines show high stability, the respective neutral radicals of N‐unsubstituted phenothiazines have never been isolated. Herein, the 1,9‐diamino‐3,7‐di‐tert‐butyl‐N1,N9‐bis(2,6‐diisopropylphenyl)‐10H‐phenothiazin‐10‐yl radical (SQH2.) is described as the first air‐stable, neutral phenothiazinyl free radical. The crystalline dark‐blue species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Of the different cation radicals, the semi benzoquinone-type radical cation species (SQH˙ + & SQ + ) are highly unstable. 50 It is vulnerable to oxidation or disproportionation into the more favorable 14-π electron quinonic (Q + ) cation system, which is stabilized by gaining aromaticity by the Huckel magic number. 51 The chemical stability of phenothiazine was also questionable as they undergo unavoidable side reactions by the radical coupling or oxidation of sulfur to sulfoxide and further to sulfone.…”
Section: Resultsmentioning
confidence: 99%
“…Of the different cation radicals, the semi benzoquinone-type radical cation species (SQH˙ + & SQ + ) are highly unstable. 50 It is vulnerable to oxidation or disproportionation into the more favorable 14-π electron quinonic (Q + ) cation system, which is stabilized by gaining aromaticity by the Huckel magic number. 51 The chemical stability of phenothiazine was also questionable as they undergo unavoidable side reactions by the radical coupling or oxidation of sulfur to sulfoxide and further to sulfone.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the antioxidant activity of phenothiazine and its derivatives is due to the formation of a stable radical cation that becomes stabilized over a large conjugative moiety, and to the change of the phenothiazine butterfly structure to a planar one. In this context, the pharmacological activity of phenothiazine core as an anticancer agent has been attributed to radical stability [ 50 ]. It is worthy of mentioning that chemical antioxidant activity was determined by a simple assay, and in vitro antioxidant activity would better reflect a closer value to the in vivo activity [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Likely due to the deprotonation and one-electron oxidation that occurred. [33] Upon completion of the reaction, a precipitate formed due to the overoxidation product being insoluble in acetonitrile.…”
Section: Optimisation Of Cpz Metabolites Electrosynthesismentioning
confidence: 99%